FROM SCROLL TO SKILL 2.0: INTEGRATING YOUTUBE AND AI TOOLS TO ENHANCE STUDENTS’ EXTENSIVE LISTENING SKILLS - Sakuta, Dodie Ardian; Jusriati; Sari, Puspa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates how the integration of YouTube and artificial intelligence (AI) tools enhances students’ extensive listening skills in English as a Foreign Language (EFL) contexts. The research addresses a key issue in digital language learning: while students frequently use YouTube for exposure to authentic language, the absence of structured scaffolding and strategy instruction often limits comprehension gains. Focusing on this problem, the study explores how AI-assisted tools—such as real-time transcription, automatic subtitles, summarization, and adaptive feedback—can transform YouTube-based listening from passive consumption into active, autonomous learning. Using a qualitative descriptive approach, data were collected through semi-structured interviews with four purposively selected students from We Learn English Students Course in Palopo, an English language training center. Data collection and analysis followed a three-phase procedure: transcription, member checking, and coding to uncover learners’ strategies, motivations, and perceived skill development. The findings reveal that AI-supported YouTube activities significantly improved learners’ comprehension, pronunciation, and self-regulated learning behaviors. Students demonstrated increased metacognitive awareness, utilizing AI tools to plan, monitor, and evaluate their listening performance. Furthermore, intrinsic motivation and learner autonomy were strengthened, as participants selected content aligned with their interests and received personalized feedback. The study concludes that AI-mediated YouTube engagement fosters a shift “from scroll to skill,” transforming entertainment-oriented digital habits into meaningful language learning experiences. The results underscore the pedagogical potential of integrating AI-driven scaffolding into extensive listening instruction to promote motivation, competence, and learner independence in EFL settings.